Collaborative work partnerships: Fuel for personal resilience. (September 2019) - Romain, Amy M; Odom, Amy J
Collaborative work partnerships bring joy and meaning to one's work. Additionally, outcomes and productivity from the partnership are often richer and more expansive, contributing more to the system and more to the profession than individuals alone. Using stories and examples from their 12-year work relationship, the authors will explore elements that contribute to successful collaboration. This article will highlight the importance of embracing vulnerability as a preparatory step to creating collaborative partnerships and will discuss a model to understand how a partnership can advance the relationship to a higher level. Finally, it will examine how relational coordination in work settings can support productive collaboration.